Early modern war narratives and the Revolt in the low countries - Fagel, R. P.; Álvarez Francés, Leonor; Belmonte, Beatriz Santiago (Studies in early modern European history., 2020)
The Revolt in the Low Countries is one of the major conflicts of early modern Europe. Though it is mostly seen as a war between the Dutch and the Spanish, in reality it was a complex civil war with international involvement. This book returns to the original war narratives of the period, re-establishing the multi-faceted character of the conflict.